Clinical effects of Bifidobacterium Longum Subsp. Infantis YLGB-1496 on children with respiratory symptoms - Li, Pin; Mageswary, Uma; Ali, Adli; Taib, Fahisham; Koo, Thai Hau; Yusof, Azianey; Jiang, Hua; Lan, Hanglian; Hung, Weilian; Liong, Min-Tze; Zhang, Yumei (Frontiers in Nutrition, 2025)
ObjectivesThis study aimed to examine the effects of Bifidobacterium longum subsp. infantis YLGB-1496 (B. infantis YLGB-1496) on the frequency of respiratory illness symptoms and immunity profiles among toddlers.MethodsIn this double-blind, randomized, placebo-controlled, 12-week intervention study, toddlers with at least 2 respiratory illness symptoms were randomly assigned into the probiotic (YLGB-1496) or placebo group at a 1:1 ratio. Follow-up examinations were conducted at baseline (week 0) and at weeks 6 and 12 of the intervention. The frequency of respiratory illness symptoms was assessed at these time points using validated questionnaires. Oral swabs and fecal samples were collected from participants at weeks 0, 6, and 12 to examine inflammatory cytokines.ResultsAmong the 120 toddlers initially included in the study, 115 completed the 12-week intervention (58 in the YLGB-1496 group and 57 in the placebo group). The risk of antibiotic use or clinical visits was significantly lower in the YLGB-1496 group than in the placebo group (antibiotic use odds ratio (OR) = 0.37 [0.369, 0.372]; clinical visit, OR = 0.743 [0.741, 0.744]), but these differences were nonsignificant after adjusting for other potential confounders (p > 0.05). The YLGB-1496 group presented a lower incidence of several respiratory symptoms than the placebo group, including fever (p < 0.001), cough (p < 0.001), sneezing (p = 0.012), nose block (p = 0.001), and runny nose (p < 0.001). The results also revealed that the salivary cortisol concentration was significantly lower in the YLGB-1496 group than in the placebo group (p = 0.026), but no effects on INF-γ, IL-1β, IL-13, IL-4, or IL-10 were detected.ConclusionBifidobacterium infantis YLGB-1496 may serve as a potential natural, nonpharmacological strategy for the safe management of respiratory tract issues in toddlers.Clinical trial registrationThe trial was registered at ClinicalTrials.gov (identifier number NCT05794815).